Comparison between the standard forms of building contract used in Nigeria and Malaysia - Mustapha, Bawa (2011)
Payment is considered as the lifeblood of the construction industry because constructions often involve very large capital outlay and take a considerable time to complete. In Nigeria, over 11,800 capital projects are abandoned as the result of non-payment or delay in payment. The research focused on payment issues aimed at identifying the differences in payment method between JCT 2009 and PAM 2006 Standard Forms, invariably recommending ways to improve payment methods in these Standard Forms. JCT 2009 Standard Form is used in Nigeria for both public and private projects while in Malaysia PAM 2006 are used for private projects and JKR 203A (Rev, 2007) is used for government projects. In Nigeria the government standard form was drafted in 1978 for public projects but was abandoned because of its deficiencies. Payment is made through the issuance of interim certificate at interval of 28 days in JCT 2009 standard Form and 21 days in PAM 2006 Standard Form. The Time of honouring interim certificate is 14 days in JCT 2009 Standard Form in PAM 2006 Standard Form is 21 days. In comparing the time of issuance and honouring certificate between PAM 2006 and JCT 2009 standard forms are the same. PAM 2006 Standard Form requires written application as mandatory. Payments on certificates are difficult in most cases because the money most of the time is used for other purpose by the employer. The research found parties to contract are not knowledgeable in construction law in Nigeria. The contractor is entitled to interest on unpaid amount due in interim certificates. The research recommended that the Nigerian government should draft its own Standard Form with, priority to offering the subject of construction law in the school’s curriculum should be emphasised, workshop for contactors on legal position of payment should be organised, interest rate be paid on unpaid amount due, adequate project budget should be made, retention fund should be kept for contractor use.